Competition and anti-dumping: Continued peaceful co-existence? - Edwin Vermulst (Fondazione Eni Enrico Mattei (FEEM), 1999)
EU anti-dumping and competition policy overlap to a certain extent in their goals and means. However, there are many differences in the aims and means of both policies, which make the relationship between both policies a multifaceted one. This paper reviews the conceptual differences between both economic policies, and attempts to consider a recent large anti-dumping proceeding from the point of view of competition policy. The conclusion is that the facts of that proceeding would clearly not be actionable under competition law. The authors believe that market access policy might be a better replacement for competition policy.
Keywords: 330; Anti-dumping; Competition; Contestability of markets; Market access; Antidumping; Wettbewerbspolitik; Potenzieller Wettbewerb; Markteintritt; EU-Staaten